2013
DOI: 10.1016/j.jcrs.2012.08.055
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes after implantation of a new hydrophobic acrylic toric IOL during routine cataract surgery

Abstract: Implantation of the new toric IOL was an effective, safe, and predictable method to manage corneal astigmatism in patients having routine cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
33
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 22 publications
8
33
4
Order By: Relevance
“…Likewise, our results in terms of predictability of refractive correction were also comparable to those reported for other modalities of toric IOLs [5][6][7][8] and in some cases even better. 9,10 Visser et al 9 found that residual refractive astigmatism of -1.00 D or less was achieved in approximately 90% of samples of eyes implanted with a toric multifocal IOL.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Likewise, our results in terms of predictability of refractive correction were also comparable to those reported for other modalities of toric IOLs [5][6][7][8] and in some cases even better. 9,10 Visser et al 9 found that residual refractive astigmatism of -1.00 D or less was achieved in approximately 90% of samples of eyes implanted with a toric multifocal IOL.…”
Section: Discussionsupporting
confidence: 90%
“…With the same type of toric IOL, Alió et al 18 obtained a mean value of IOL rotation of 3.35° ± 3.56°. Sheppard et al 5 found a mean absolute IOL misalignment from the intended axis of 3.4° (range: 0° to 12°) in a sample of eyes implanted with the Tecnis toric IOL (Abbott Medical Optics, Inc., …”
Section: Discussionmentioning
confidence: 99%
“…(20) Such vectorial astigmatism analysis is gaining popularity in literature in recent years, as an increasing number of articles employ it as analytical instrument. (1,4,7,8,21,22) Figure 4 compares mean magnitudes of pre and postoperative APV within each group and between groups. A statistically significant reduction in APV, considering preoperative and any postoperative APV, was found within each group (p value = 0.00).…”
Section: Discussionmentioning
confidence: 99%
“…If the eye scheduled for cataract surgery has a significant astigmatism, postoperative vision will be impaired by this refractive error, and patient will need spectacles to obtain adequate distance and near vision. For patients with significant astigmatism, solution was found with the invention of toric IOLs, which were designed for two functions: to restore visual acuity deteriorated by cataract and to correct corneal astigmatism [9][10][11][12][13]. Toric IOLs must be produced individually since each eye with the corneal astigmatism has a unique combination of spherical and astigmatic correction (regarding both the amount and the axis of astigmatism).…”
Section: Introductionmentioning
confidence: 99%